KOREOGRAFI IMBAUAN LASUANG - Nova Astira; Martion Martion; Susas Rita Loravianti (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2017)
ABSTRACT The dance of “Imbauan Lasuang” is inspired by the social phenomena of Padang Laweh people that comes from alu ketentong combined with the phenomenon of local culture. Previously in Padang Laweh people, alu ketentong functioned as an exclamation in the village in order to communicate cultural events that will be done in society. Communication is the requirement for the occurrence of social interaction but recently, means of communication by using alu ketentong is started to be forgotten and ignored. The influence of high technological improvement results on the lack of social interaction among people. Therefore there is a boundary wall in direct communication that leads to westernized lifestyle with its system of individual life. This phenomenon then becomes the inspiration for creating this choreography materialized through Minangkabau local idioms such as silat movements. Keywords: Alu ketentong, communication, Padang Laweh